Calculation of the Cost of Production in Determining the Selling Price of Kelle Soap Products Sari Amertha Aan - Luh Ayu Prastista Artami; I Ketut Sudiartha; I Gede Made Karma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
Determining the selling price of a product based on the cost of production can help find out what the right product selling price is to cover all production costs. This study aims to determine the calculation of the cost of production using the full costing method and to determine the calculation of the selling price set by the Soap Kelle Sari Amertha Business and the selling price based on the calculation of the cost of production according to the full costing method. This research was conducted at the Soap Kelle Sari Amertha Business located in Banjar Petapan, Aan Village, Banjarangkan, Klungkung. The type of research used is qualitative research through interview and observation data collection techniques with data sources using primary data. The data analysis technique in this study is the full costing method. The results of this study indicate that the cost of production according to the Soap Kelle Sari Amertha Business and the cost of production according to the full costing method obtain different results so that there is a difference of Rp 5,825. The comparison of selling prices also shows that there is a difference in results between the selling price according to the Soap Kelle Sari Amertha Business and the selling price according to the calculation of the cost of production based on the full costing method.